Why do German Firms Subsidize Apprenticeship Training? Tests of the Asymmetric Information And Mobility Costs Explanation - Damon Clark (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
It is often observed that despite the famous prediction of Becker (1962) that firms will not pay for general training, German firms do in fact subsidize apprenticeship training. This paper examines two prominent solutions to this puzzle - "asymmetric information" and "mobility costs." Our tests do not support the asymmetric information hypothesis, and, while they provide evidence consistent with a simple mobility cost explanation, we argue that this hypothesis is deficient in a number of other respects.
Keywords: 330; Betriebliche Ausbildung; Arbeitsmobilität; Ausbildungsfinanzierung; Asymmetrische Information; Deutschland